Respiratory disease in non-smoking Western Australian goldminers. Issue 11 (November 1992) - Musk, A W; Rouse, I L; Rivera, B; de Klerk, N H; McNulty, J C
Abstract : Respiratory symptoms, spirometry, and transfer factor were measured in 208 non-smoking Western Australian underground goldminers (mean age 32) to identify the presence of respiratory abnormalities resulting from underground work. These subjects were part of a larger group of 771 subjects attending for statutory periodic chest x ray examinations in the industry. They had worked underground for a median of three years. The prevalence odds ratios of bronchitis, dyspnoea, wheeze, and asthma all tended to be related to duration of underground employment, even after adjusting for age, those for wheeze and asthma reaching statistical significance. After adjusting for age and height the duration of employment also had a significant effect on TL/VA but not on FEV1, FVC, or TL. These changes are consistent with the presence of airway narrowing and non-specific lung fibrosis or emphysema in non-smoking underground goldminers.